2009
DOI: 10.1590/s1413-81232009000600031
|View full text |Cite
|
Sign up to set email alerts
|

Exposição a pesticidas e repercussão na saúde de agentes sanitaristas no Estado do Ceará, Brasil

Abstract: Exposição a pesticidas e repercussão na saúde de agentes sanitaristas no Estado do Ceará, BrasilPesticide exposure and its repercussion in the health of sanitary agents in the State of Ceará, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
0
11
0
8
Order By: Relevance
“…Next, 29 studies showed the multi-causality of the illness process in which the diseases studied were approached from the perspective of risk factors and in the interlocution of biological aspects with psychological, social, and individual behavior 2,25 . Part of the works presented sociodemographic data and the relationship between work and health in some sectors of the economy, with emphasis on mining, agribusiness (sugar and alcohol, timber), transportation, electricity, fishermen and crab scavengers, services (bank, police, and military, health professionals, and garbage collectors), and industry (especially metallurgists).…”
Section: Methodsmentioning
confidence: 99%
“…Next, 29 studies showed the multi-causality of the illness process in which the diseases studied were approached from the perspective of risk factors and in the interlocution of biological aspects with psychological, social, and individual behavior 2,25 . Part of the works presented sociodemographic data and the relationship between work and health in some sectors of the economy, with emphasis on mining, agribusiness (sugar and alcohol, timber), transportation, electricity, fishermen and crab scavengers, services (bank, police, and military, health professionals, and garbage collectors), and industry (especially metallurgists).…”
Section: Methodsmentioning
confidence: 99%
“…Outro cenário possível é que os gestores públicos não disponibilizem o EPI. Candido e Ferreira (2017) revelaram que existe uma baixa adesão aos EPI por parte desses profissionais e, de acordo com Lima et al (2009), foi constatado em seus estudos que a instituição responsável raramente fornecia os EPI e, quando disponibilizava, esses equipamentos apresentavam qualidade ruim e em número insuficiente, e quando havia o desgaste não era feita a reposição.…”
Section: Categoria 03 -Principais Fatores Que Dificultam O Combate Aounclassified
“…Muito embora não tenham sidos mencionados na presente pesquisa, consideramos importante citar outras dificuldades listadas por Ferreira Junior, Torres e Silva (2015) ao realizar um estudo para identificar doenças, acidentes de trabalho e queixas relacionadas aos ACEs. Eles constataram que todos os participantes da pesquisa foram expostos a produtos químicos, o que está em concordância com Lima et al (2009) que afirmam ser essa categoria profissional vulnerável aos efeitos dos inseticidas. Ferreira Junior, Torres e Silva (2015) acrescentam queixas como exposição solar risco de violência urbana; trabalho realizado em altura com risco de queda; peso da bolsa que precisam, carregar na rotina de trabalho; e a falta de reconhecimento profissional por parte da comunidade e instituições às quais prestam serviço.…”
Section: Categoria 03 -Principais Fatores Que Dificultam O Combate Aounclassified
“…The chemical control of mosquitoes using insecticides and larvicides raises concerns for the health of the people who have to apply the products (Lima et al 2009), damages to the environment (Fournet et al 1993), and selects for resistant mosquito strains (Andrade and Santos 2004). An alternative currently adopted in many parts of the globe is the biological control of mosquito larvae using copepods (French Polynesian islands: Rivière et al 1987, Lardeux et al 1992; in New Orleans, US: Marten 1990; Honduras: Marten et al 1994).…”
Section: Introductionmentioning
confidence: 99%